2004
DOI: 10.1200/jco.2004.07.124
|View full text |Cite
|
Sign up to set email alerts
|

Residual Tumor Resection After High-Dose Chemotherapy in Patients With Relapsed or Refractory Germ Cell Cancer

Abstract: Resections of all residual tumors should be attempted in patients with relapsed or refractory GCT and partial remissions after HDCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(37 citation statements)
references
References 19 publications
1
32
1
3
Order By: Relevance
“…10 The histologic findings after multiple chemotherapy regimens differ substantially from those generally reported for RPLND after induction chemotherapy, in which approximately 40% to 45% of patients have fibrosis, 40% to 45% of patients have teratoma, and 10% to 20% have viable GCT. 11,12 For RPLND after multiple chemotherapy regimens, the largest series of patients, which was reported in 1993 by Fox et al, 5 had 55% with viable GCT, consistent with 2 subsequent studies by Hendry et al 6 and Rick et al, 7 which showed rates of 42% and 49%, respectively. In the current study, there were 4 important findings for patients undergoing RPLND after multiple chemotherapy regimens.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…10 The histologic findings after multiple chemotherapy regimens differ substantially from those generally reported for RPLND after induction chemotherapy, in which approximately 40% to 45% of patients have fibrosis, 40% to 45% of patients have teratoma, and 10% to 20% have viable GCT. 11,12 For RPLND after multiple chemotherapy regimens, the largest series of patients, which was reported in 1993 by Fox et al, 5 had 55% with viable GCT, consistent with 2 subsequent studies by Hendry et al 6 and Rick et al, 7 which showed rates of 42% and 49%, respectively. In the current study, there were 4 important findings for patients undergoing RPLND after multiple chemotherapy regimens.…”
Section: Discussionsupporting
confidence: 67%
“…When RPLND is performed in this setting, it has been reported that viable GCT occurs in approximately 50% of patients. [5][6][7] Because of the high proportion of men with viable GCT or teratoma after salvage chemotherapy, surgical resection of all disease sites is attempted when feasible. The objectives of the current study were to review the Memorial Sloan-Kettering Cancer Center experience with RPLND after multiple chemotherapy regimens and specifically evaluate the clinicopathologic and treatment trends in addition to potential predictors of disease-specific outcome.…”
mentioning
confidence: 99%
“…In retrospective series, the reported proportion of patients with viable cancer in resected masses who suffered a relapse and underwent salvage chemotherapy was as high as 70% [30,31,32,33,34]. …”
Section: Resultsmentioning
confidence: 99%
“…When rPLa is performed in this setting, it has been reported that VC occurs in approximately 50% of patients 5,6,7 . Because of the high proportion of men with VC or teratoma after salvage chemotherapy, surgical resection of all disease sites is attempted when feasible.…”
Section: Introductionmentioning
confidence: 99%